The Role Of Corticosteroid Administration On The Incidents Of Asphyxia Neonatorum Among Mothers With Preterm Delivery In Ponek Rsud Jombang - Rini Hayu Lestari; Niken Grah Prihartanti; Mamik Ratnawati (Jurnal Ilmiah Kesehatan, 2021)
The causes of death for newborns 0-6 days in Indonesia are 36.9% respiratory disorders, 32.4% premature birth, 12% sepsis, 6.8% hypothermia, and 6.6% neonatal jaundice. A preliminary study in Comprehensive Emergency Services Neonatal Obstetric (PONEK) of Jombang Regional Public Hospital (RSUD Jombang) reported that the incidence of asphyxia neonatorum was 295 cases in 2016 and 341 cases in 2015. There were 98 cases of preterm delivery in 2016. This study aims to prove the effect of corticosteroid administration on neonatal asphyxia in mothers with preterm delivery. This study was an analytical study using a one-group after only design. The population was all women giving birth at RSUD Jombang with preterm labor diagnosis in January-May 2017, while the sample was 82. The instruments utilized questionnaires and checklists. The bivariate analysis applied the chi-square association test. Based on the results of the chi-square test χ2= 4.622> χ2 table; p = 0.009 <α (0.05). There was a correlation between corticosteroid administration and the incidence of asphyxia neonatorum in women with preterm delivery. This study's results could be an input for primary health care facilities to prevent neonatal asphyxia. Further research should develop other similar variables and increase the number of respondents.